On the Castelnuovo-Mumford regularity index of the coordinate ring of a set of n + 3 non-degenerate fat points in projective space Pn - Thiện, Phan Văn; Sinh, Trần Nam; Quang, Nguyễn Thanh (Hue University Journal of Science: Natural Science, 2021)
In this paper we calculate the Castelnuovo-Mumford regularity index of the coordinate ring of n + 3 a set of non-degenerate fat points in Pn for almost all of cases.